1997
DOI: 10.1002/(sici)1098-2361(1997)16:1<17::aid-zoo4>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Body weights of wild and captive lemurs

Abstract: The mean body weight of a species is often used as a summary measure of size in evolutionary and functional studies. Additionally, body weight is often used to assess the health of captive animals. Contrasts of the captive and wild body weights of a species can be used to examine the effects of captivity on the species. We provide an analysis of adult body weight in nine taxa of Malagasy lemurs. We compare weights of wild and captive lemurs and provide analyses of relationships between captive weight variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…In contrast, there are few sexual differences in the body masses of prosimian species, regardless of their social systems (Kappeler 1990(Kappeler , 1991Terranova and Coffman 1997;Wright 1999;Müller 1999;Sauther et al 2002;Cuozzo and Sauther 2004). In the present study, we found no sexual difference in the body mass of adult ring-tailed lemurs; this is consistent with observations from previous studies (e.g., Kappeler 1991).…”
Section: Body Mass Of Ring-tailed Lemurssupporting
confidence: 92%
“…In contrast, there are few sexual differences in the body masses of prosimian species, regardless of their social systems (Kappeler 1990(Kappeler , 1991Terranova and Coffman 1997;Wright 1999;Müller 1999;Sauther et al 2002;Cuozzo and Sauther 2004). In the present study, we found no sexual difference in the body mass of adult ring-tailed lemurs; this is consistent with observations from previous studies (e.g., Kappeler 1991).…”
Section: Body Mass Of Ring-tailed Lemurssupporting
confidence: 92%
“…obs. ; Terranova and Coffman 1997). Eulemur rubriventer has a head-body length of 35-40 cm and a tail length of 43-53 cm.…”
Section: Focal Speciesmentioning
confidence: 99%
“…Eulemur rubriventer has a head-body length of 35-40 cm and a tail length of 43-53 cm. Body mass is 1.6-2.4 kg (Glander et al 1992;Terranova and Coffman 1997).…”
Section: Focal Speciesmentioning
confidence: 99%
“…Females known to have been pregnant at the time of weighing were excluded from analyses. The possibility of pregnancy of some females in the dataset acquired through the questionnaire could not be excluded (available data did not provide reliable information on pregnancies); however, neither Schaaf & Stuart (1983) nor Terranova & Coffman (1997) found differences in captive lemur body weights among seasons, which suggests that differences in weight between pregnant and non-pregnant females of these seasonally breeding species may not be significant.…”
Section: Methodsmentioning
confidence: 99%
“…Cousins 1972, Walike et al 1977, Savage et al 1993, Schwartz et al 1993, Encarnación & Heymann 1998, Araújo et al 2000, Chen et al 2002, Schmidt 2004, Videan et al 2007), particularly in Malagasy lemurs (Schaaf & Stuart 1983, Pereira & Pond 1995, Schwitzer & Kaumanns 2001a, Willis et al 2009). Terranova & Coffman (1997) conducted a quantitative study on a large sample of lemurs and found significant differences in weights between wild and captive individuals, with 9 species and subspecies showing obesity rates of between 17 and 95% in captivity.…”
Section: Introductionmentioning
confidence: 99%